Analysis Of The Implementation Of Complete Systematic Land Registration (PTSL) In Realizing Land Ownership Legalization In Sukoharjo Regency - Adellia Nanda Hapsari Sudaryo (Faculty of Law, Universitas Negeri Semarang, 2025)
This research is motivated by the problem of multiple certificates that arise due to weak administrative systems, lack of supervision, and inaccurate data at the National Land Agency (BPN). This condition causes legal uncertainty, agrarian conflicts, and decreased public trust in the land system. Inequality in land ownership and information distribution also worsens the situation, especially amidst the increasing need for land. This study aims to analyze the implementation of Complete Systematic Land Registration (PTSL) and its impact on land law in Sukoharjo Regency. The method used in this study is an empirical legal approach with qualitative research through observation, interviews with the Head of the General and Personnel Section of the Sukoharjo BPN, and documentation studies. The results of the study indicate that the implementation of PTSL is carried out systematically through stages starting from budget allocation, counseling, committee formation, measurement, filing, legal verification, land inspection, to the issuance and submission of certificates. The success of the program is largely determined by coordination between agencies, community participation, and legal and security supervision. However, there are still obstacles such as bad weather and difficulty finding landowners. Routine evaluations are carried out so that targets are achieved on time. The conclusion of the study emphasizes the need for more intensive socialization of land certification, strengthening dispute mediation, optimizing certificates as collateral through banking education, and government assistance in managing land assets to support legal, social, and economic justice.